Sure, or unsure? Measuring students' confidence and the potential impact on patient safety in multiple-choice questions. (2nd November 2017) - Rangel, Rafael Henrique; Möller, Leona; Sitter, Helmut; Stibane, Tina; Strzelczyk, Adam
Abstract: Background: Multiple-choice questions (MCQs) provide useful information about correct and incorrect answers, but they do not offer information about students' confidence. Methods: Ninety and another 81 medical students participated each in a curricular neurology multiple-choice exam and indicated their confidence for every single MCQ. Each MCQ had a defined level of potential clinical impact on patient safety (uncritical, risky, harmful). Our first objective was to detect informed (IF), guessed (GU), misinformed (MI), and uninformed (UI) answers. Further, we evaluated whether there were significant differences for confidence at correct and incorrect answers. Then, we explored if clinical impact had a significant influence on students' confidence. Results: There were 1818 IF, 635 GU, 71 MI, and 176 UI answers in exam I and 1453 IF, 613 GU, 92 MI, and 191 UI answers in exam II. Students' confidence was significantly higher for correct than for incorrect answers at both exams ( p < 0.001). For exam I, students' confidence was significantly higher for incorrect harmful than for incorrect risky classified MCQs ( p = 0.01). At exam II, students' confidence was significantly higher for incorrect harmful than for incorrect benign ( p < 0.01) and significantly higher for correct benign than for correct harmful categorized MCQs ( p = 0.01). Conclusions: We were pleased to see that there were more informed than guessed, more uninformed than misinformed answers and higher students' confidence for correct than for incorrect answers. Our expectation that students state higher confidence in correct and harmful and lower confidence in incorrect and harmful MCQs could not be confirmed.